Reducing Social Disintegration and Economic Inequality through Community-Based Program for a More Equitable Society - Machdum, Sari Viciawati; Harisoesyanti, Kania Saraswati; Rukminto Adi, Isbandi (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2024)
Since the independence of Indonesia, many problems have always been discussed. Poverty and inequality are one of those problems that existed and have been solved since almost eight decades ago. The government has been trying to make the country better through development that emphasizes economic improvement. Unfortunately, economic development creates another social problem: the gap between the “haves” and the “have-nots.” Social and economic disparities could cause social disintegration. The main dispute is not merely in the poverty itself, but how the stakeholders respond to poverty. This article examines the problems of poverty from the community integration point of view. We found how communities can become separated from each other due to various factors such a physical, social, and economic barriers. It outlines the challenges faced in addressing social disintegration through the children's learning house program which is based on community-based action research.